Answers

  • apl
  • Ambitious
2015-04-11T09:52:49+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
4x2-4x+1
=4x2-(2+2)x+1
=4x2-2x-2x+1
=2x(2x-1)-1(2x-1)
=(2x-1)(2x-1)
0
i hpe it hlped u:)
how +1 changed into -1 in the 3 step
see we took minus common so as u knw -+- =-
i hope u undrstd frnd:)
2015-04-11T10:44:24+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
⇒ 4x2-4x+1
⇒ 4x2 –  2x –  2x +1
⇒ 2x[2x – 1] – 1[2x – 1]
⇒ [2x– 1] [2x– 1]

0
oyy
why u r roported??
if u have another mathod for solving this??
But you can write better tgan the previous answer !
how?? tell me and not copy form thet